Validation of Problem-Based Learning Videos on Environmental Pollution Material for Class VII SMP NU Palangkaraya - Khusna, Nur; Sa’adah, Ayatus; Rohmadi, Mukhlis (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
Media in the form of problem-based learning videos (PBL) is very necessary when learning material related to environmental pollution. This research aims to see the feasibility of learning videos based on material problems related to environmental pollution, as proven by the evaluation results of validation experts, namely material validators and media validators. This research was conducted on 26 class VII students at SMP NU Palangkaraya. The method used in this research is Research and Development (R&D) which adopts the ADDIE (Analyze, Design, Develop, Implement, Evalute) development model. The media developed by researchers is designed based on the parameters of problem-based learning activities. The validation results from the material and media validators show that the criteria are feasible, with percentages of 74% and 88.9 % respectively. Based on the results of this research, it can be concluded that problem-based learning videos on environmental pollution material are suitable for use in learning.